A Culturally Responsive PAI Learning Design: Integrating Local Islamic Wisdom through Meaningful and Engaging Student Participation - Sinta Bella; Irawan Irawan (Abjadia : International Journal of Education, 2026)
This study aims to develop a learning design that is relevant to local Islamic culture, so that students can actively engage in a meaningful and enjoyable learning process. The background of this study stems from the need for a learning model that not only emphasizes academic achievement but also pays attention to Islamic values and local culture as part of the formation of student character. In the context of education in Indonesia, the diversity of local Islamic culture and traditions is a great potential that can be integrated into the learning process to make it more contextual, authentic, and close to the daily lives of students. The method used is the library research method by reviewing various relevant literature sources, such as books, journals, and previous research results on learning design, local Islamic culture, and meaningful and enjoyable learning strategies. Learning design that is relevant to local Islamic culture and actively involves students can be an alternative effective learning strategy to build a contextual and enjoyable learning experience. Such learning not only strengthens students' Islamic identity, but also fosters a love for local culture and develops critical, social, and spiritual thinking skills in a balanced manner.